EXPLORING THE DETERMINANTS OF ONNLINE SHOPPING CONSUMPTIVE BEHAVIOR: A LITERATURE REVIEW FORM THE SOR THEORY PERSPECTIVE - Mirawati, Mirawati; zainol, Zuraidah binti; Mahmud, Amir; Siska, Maya; Putra, Rahmad Ade (Economic and Science Faculty of Islamic State University, 2025)
This literature review examines the factors influencing online consumptive buying behavior, with a particular focus on lifestyle, financial literacy, self-control, religiosity, within the framework of the Stimulus-Organism-Response (SOR). It highlights the interaction of the interaction among these variables in shaping online consumer decisions, making, where lifestyle, financial literacy and self-control function as primary psychological stimuli, and religiosity acts as an internal filter. The review underscores a research gap concerning specific cultural contexts, particularly West Sumatera, where traditional cultural and religious values significantly influence consumer behavior. This paper proposes directions for future research, including the uses mixed-method approaches and longitudinal studies to further explore these dynamics in local settings